Scoping review of intergenerational learning methods for developing digital competence and their outcomes - Mira Hammarén; Erika Jarva; Kristina Mikkonen; Maria Kääriäinen; Outi Kanste (Finnish Social and Health Informatics Association, 2022)
Due to the rapid digitalization of healthcare, it is important to strengthen professionals' digital competence, particularly to support older professionals to stay in work until retirement age. People of different ages have different digital competencies. Younger generations are 'digital natives' who have learned to use digital devices fluently from a young age, while older generations have had to learn to use them in adulthood. The increasing number of new technologies causes in some cases stress, especially for more older healthcare workers. Intergenerational learning methods for developing digital competence may offer a way to narrow digital competence gaps in healthcare. The aim of this scoping review was to identify current evidence regarding intergenerational learning methods for developing digital competence, and their outcomes. The results can be used to help develop methods for intergenerational digital competence development and improve healthcare professionals' digital competence. A scoping review was conducted across four databases (Scopus, CINAHL, Web of Science, ProQuest) without time limits. The search produced 2905 references, of which 23 studies are included in the review. Thematic analysis was used to analyze these studies' results. The results showed that a key method for intergenerational digital competence development is reverse mentoring, where a less experienced person serves as a mentor to a more experienced one. Intergenerational digital competence development methods can be done one-on-one or in groups, in classes or on digital platforms. The outcomes of these methods illustrated that they promote mutual learning, increase the digital competence of older adults and the work life skills of young mentors, and narrow the gap between generations. Using such methods, it is possible to make better use of each generation's expertise. Intergenerational learning could suggest ways of narrowing the digital gap and enhancing intergenerational communication. Healthcare could benefit from implementing intergenerational learning methods for developing digital competence, increasing the digital competence of healthcare professionals, and narrowing the gap between generations.